Loose coordination and relocation in a South-South value chain: cashew processing and trade in southern India and Ivory Coast - Tessmann, Jannes; Fuchs, Martina (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
This article is concerned with a crucial part of the cashew nut value chain which links raw cashew nuts to processing. We focus on the interactions of intra-chain governance and its institutional context. The central question is how the raw cashew nut value chain is coordinated and relocated as a response to its changing institutional environment. Using a qualitative methodological approach, the contribution shows the dynamics of loose chain coordination and relocation in India and Ivory Coast.